Does social media influence consumer decision-making in times of the COVID 19 pandemic. - Meerakkuddy Siraji; MS. Ishar Ali (Daengku: Journal of Humanities and Social Sciences Innovation, 2021)
The main objective of this study is to examine the effect of social and traditional media on customer decision-making and to find out which of these two in times of pandemics affect more on customer decision-making. A survey was conducted using 250 respondents from Ampara District, Sri Lanka, aged between 20-30. The questionnaires were divided equally into three sets, the first part containing social media-related questions, the other part containing conventional media related questions, and the third aspect of customer decision-making. Results from a survey of 250 young people in Ampara, Sri Lanka show that in times of pandemic where both social and traditional media affect consumer decision-making but social media influence is much greater than the traditional media. The findings show that advertisers need to carefully pick the media to communicate with target customers in order to achieve their marketing communication goals.